Chronic eczema. The search for treatment of severe forms - Vyacheslav V. Starostenko; Olga An. Sidorenko; Lyudmila P. Sizyakina; Elizaveta Ev. Sidorenko (Медицинский вестник Юга России, 2019)
Objective: to study the clinical efficacy of re-PUVA therapy in patients with torpid forms of chronic true hand eczema. Materials and methods: the study involved 78 patients (47 women, 31 men) with severe and moderate forms of chronic true hand eczema. Clinical indices were used before and after treatment: HECSI, DLQI. The patients were randomly divided into 3 groups: 1 group (25 people) received standard therapy (antihistamines, external glucocorticosteroid drugs, emollients); 2 group (27 people) received the indicated standard therapy against the background of PUVA; Group 3 (26 people) -standard therapy on the background of re-PUVA (combination of PUVA with retinoids (isotretinoin)). The duration of therapy was about 3 months. Results: in group I, before treatment, the average value of the HECSI index was 76.0 ± 37.9, and after the treatment, 63.6 ± 30.2; in group II, before treatment, the average value of the HECSI index was 78.3 ± 34.2, and after treatment it decreased to 51.5 ± 24.0, in group III, respectively, before treatment, the average HECSI was 77.2 ± 35.3, and after course of therapy 28.7 ± 14.0. The duration of remission in the first group after a course of standard therapy was 2.52 ± 1.1 weeks, in the second group 15.7 ± 7.5 weeks, in the third group 61.7 ± 32.4 weeks. Conclusions: The re-PUVA method is most effective in the treatment of chronic eczema of the hands in comparison with the PUVA and standard therapy.